ANALYSIS OF THE EFFECT OF LEGAL SOCIOLOGY WITH LAW LOCATED IN SOCIETY - Muljadi, Aldo Ravellio (International Journal of Research -GRANTHAALAYAH, 2019)
The Sociology of Law is a part of the science of law that examines the interrelationships or the mutual influence between law and social phenomena which is carried out analytically and empirically. Sociology of Law becomes a benchmark in society whether the law to be formed can live in society, and also whether the law that has lived in society becomes law which can then become a legal certainty. The sociology of law can also be a factor of social control, which can then control the norms that exist in society. The results of this study explain that the sociology of law has an influence in the formation of existing laws in society. Because like Roscoe Pond said that "Law is a tool of social engineering" that is law as a tool for social engineering or the community.